Nilai-Nilai Edukatif Tentang Hidup Sederhana Perspektif Al-Qur’an Surat Al-Isra’ Ayat 29 Kajian Ilmu Pendidikan Islam - Sulaiman, Husnan; Asadiyah, Pasa Zulpa Nabila (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
The current reality is that many individuals do not fully grasp how the principles of frugal living are articulated in the Qur'an. People often spend their resources freely, without reflecting on the implications and advantages of their purchases. While a fondness for wealth is not inherently negative, it can lead to complacency, greed, and stinginess. The Qur'an serves as a guiding framework for humanity, embedding essential values that promote high ethical standards and morals, including the admonition against being miserly and wasteful. This study aims to elucidate the educational values associated with simple living as interpreted from the Qur'an, specifically Surah Al-Isra' verse 29, and to explore the implications of Islamic education in daily life. The research methodology employed is a literature review, which involves examining various texts, commentaries, journals, and other relevant publications on the subject matter. A qualitative research approach is utilized, focusing on content analysis of Surah Al-Isra' verse 29 and its interpretations. The findings of this study reveal that Surah Al-Isra', verse 29, conveys significant moral teachings, advocating for a simple lifestyle while discouraging stinginess and extravagance in financial matters. This verse illustrates that the most prudent way to utilize one's wealth is through frugality, decency, and rationality. Consequently, Islam encourages individuals to lead a simple life, emphasizing a balance between worldly pursuits and spiritual obligations. Within the realm of Islamic education, these values contribute to the development of virtuous character in the management and expenditure of wealth. Islamic education encompasses the principles of instilling religious values to nurture faith and devotion to Allah SWT. It is important to note that Islamic education is intrinsically linked to character education, as both aim to cultivate a character that is devoted and pious towards Allah SWT.  Keywords: educational values, simple living, Islamic education